2019
DOI: 10.17576/mh.2019.1401.08
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Stingless Bee Honey and Its Effect on the Viability of Lymphoblastoid Cell Line

Abstract: Penyelidikan madu lebah (kelulut madu) merupakan bidang baru dalam penyelidikan perubatan. Walaupun ia telah digunakan sebagai makanan tradisional dan tambahan selama berabad-abad, pengetahuan mengenai potensi kesihatannya secara saintifik dan terutama pada sifat antioksidannya masih sedikit. Sifat-sifat antioksidan madu diukur dengan menggunakan asai potensi pengurangan ferio, dan mengukur jumlah kandungan fenol dan flavonoid menggunakan spektrofotometri UV. Kandungan jumlah fenolik, jumlah kandungan flavonoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Interestingly, the disruptive effects of PS-MPs on uterine morphology were restored by concurrent treatment with Kelulut honey, which approximated normal histology. In addition to the carbohydrates, amino acids, proteins, organic acids, vitamins, and various phytochemicals contained in Kelulut honey, the improvement can be explained by the high content of natural antioxidants in honey [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the disruptive effects of PS-MPs on uterine morphology were restored by concurrent treatment with Kelulut honey, which approximated normal histology. In addition to the carbohydrates, amino acids, proteins, organic acids, vitamins, and various phytochemicals contained in Kelulut honey, the improvement can be explained by the high content of natural antioxidants in honey [48].…”
Section: Discussionmentioning
confidence: 99%
“…increased antioxidant defenses, elevated Nrf2 expression, and decreased lipid peroxidation and oxidative DNA damage [50]. In addition, Kelulut honey has been shown to reduce oxidative stress (a precursor of DNA damage) in lymphoblastoid cell lines (LCLs) through its free radical scavenging activities (phenolic and flavonoid chemicals) [48]. Furthermore, Kek et al reported that Kelulut honey possesses higher phenolic content and has the highest antioxidant levels compared with Tualang and Gelam honey [17].…”
Section: Discussionmentioning
confidence: 99%
“…enhanced anti-oxidant defenses, upregulated Nrf2 (protein that regulates the expression of antioxidant proteins), and reduced lipid peroxidation and oxidative DNA damage in in vivo study using Sprague Dawley rats. In addition, an in vitro study conducted by Abdul Karim [ 42 ] found that KH reduced the oxidative stress (precursor to DNA damage) in lymphoblastoid cell line (LCL) through its free radical scavenging activity (phenolic and flavonoid compounds). However, the protection to DNA damages by KH was only limited to irradiation doses below 20 Gy (11 Gy–19 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity was measured using DPPH assay. 9 About 100 µL of the samples at different concentrations were mixed with the DPPH solution (Sigma-Aldrich, USA). The sample solutions were kept at room temperature for 30 mins.…”
Section: Dpph Scavenging Activitymentioning
confidence: 99%
“…About 7 mM of ABTS stock solution (Sigma-Aldrich, USA) was mixed with 2.45 mM ammonium persulphate (Sigma-Aldrich, USA) and incubated in the dark for 16 hours at room temperature. 9 Prior to assay, the mixture absorbance was adjusted to give 0.70±0.05 at 750 nm. ALLURA™ extract (30 µL) was added to 300 µL of ABTS working solution and let to stand in the dark for 6 min.…”
Section: Abts Radicals Assaymentioning
confidence: 99%